Thank you, I'll try to understand that and maybe use it later]]>

By the rule of signs, there is one sign change, so there is a positive root, so start with positive numbers.

After finding that 3 is a root, we know that we can factor out (x-3)

Use synthetic division to find out the remaining quadratic:

]]>x³-9-6x=0

(x³-27)+18-6x=0

(x-3)(x²+27x+27²)-6(x-3)=0

(x-3)(x²+27x+723)=0

x-3=0

x=3

and

x²+27x+723=0

D<0 no solutions

Now the answer is correct.

Could u explain me how you get this (x^2+3*x+3)?

]]>We can factor out (x-3) from here, leaving

(x-3)(x^2+3*x+3) = 0

x-3 = 0, so x=3 is a solution

x^2 + 3x + 3 = 0

This can be solved easily using the quadratic formula

x³=6x+9

It doesn't seem difficult, but my answer doesn't suit to the answer in the book

]]>